«Militaria Byzantina» в Таврике (по данным моливдовулов) - Алексеенко, Н.А. (Боспорские исследования, 2009)
Although the molybdoboulloses of the representatives of the military department do not occupy any leading place among total quantity of Byzantine hanging seals found in the Crimea, they are represented by various categories of the army and naval organization men. Absolute majority of the seals belong to local commanders from Cherson (over one hundred and twenty items) and Sugdeya (three ones); Gothic turmarch can be also included in this category - two items. Finds of seals belonging to military leaders of some north Pontic area and Mediterranean region femas are known. They are seals of the commit Opsikius, stratiges of Thessalonica, Hellas, Sicily, Macedonia, Anatolia, etc.